How long does it take? Reliable personality assessment based on common behaviour in cotton-top tamarins (Saguinus oedipus) - Masilkova, Michaela; Weiss, Alexander; Konečná, Martina (Behavioural processes, 2018)
Individual variation in behaviour has been shown to have important ecological and evolutionary consequences. Research on animal personality has therefore received considerable attention, yet some methodological issues remain unresolved. We tested whether assessing personality by coding common behaviours is as time-consuming method as some researchers believe it to be. Altogether, 300 hours of observation were collected on 20 captive cotton-top tamarins (Saguinus oedipus). We first examined the repeatability of behavioural indices that represented the behavioural repertoire of cotton-top tamarins. We then compared the personality structures, based on different lengths of observation time, of these behavioural indices. The minimum observational time necessary to obtain a stable personality structure was 5 to 7 hours per individual. This stable structure included two components: Extraversion and Confidence, which were similar to those described in great apes, Old World monkeys, and other New World monkeys. Our findings suggest that, at least in the case of cotton-top tamarins, behavioural coding over relatively short periods of time can be used to assess personality and that longer observation periods may yield diminishing returns.
Keywords: Animals; Personality Assessment; Female; Animal personality; ženské pohlaví; Time Factors; časové faktory; testování osobnosti; chování zvířat; Behavioural observation; Saguinus; Callitrichidae; Male; Individuality; Continuous focal recording; Behavior, Animal; individualita; mužské pohlaví; zvířata; Consistency